1965
DOI: 10.1037/h0022318
|View full text |Cite
|
Sign up to set email alerts
|

Adequate acoustic stimulus for startle reaction in the cat.

Abstract: The absolute threshold for startle was obtained as a function of primary dimensions of pure ; tone: frequency, rise time, and duration. Individual rat's thresholds were measured using the up-down technique. Response latency (16 msec.) exhibited little variability under all experimental conditions. Startle sensitivity increased with tone frequency; this function seemed to reflect the sensitivity of the rat's ear. From the results of the rise time and duration experiments, it was concluded that the tone's peak i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
46
0
4

Year Published

1974
1974
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(53 citation statements)
references
References 12 publications
3
46
0
4
Order By: Relevance
“…The amplitude of the acoustic startle reflex in the rat (Fleshler, 1965) and in the human (Berg, 1974) is related to the tonal frequency of the eliciting stimulus (Foss, 1985), its intensity (Hoffman & Searle, 1968), duration (Marsh, Hoffman, & Stitt, 1973), rise time (Ison, 1978), and repetition rate (Davis, 1970). In addition, lawful modification of the startle reflex results from varying the intensity and lead time of sensory stimuli presented prior to or accompanying the eliciting stimulus (Hoffman & Searle, 1968;Ison & Hammond, 1971;Krauter, Leonard, & Ison, 1973).…”
mentioning
confidence: 99%
“…The amplitude of the acoustic startle reflex in the rat (Fleshler, 1965) and in the human (Berg, 1974) is related to the tonal frequency of the eliciting stimulus (Foss, 1985), its intensity (Hoffman & Searle, 1968), duration (Marsh, Hoffman, & Stitt, 1973), rise time (Ison, 1978), and repetition rate (Davis, 1970). In addition, lawful modification of the startle reflex results from varying the intensity and lead time of sensory stimuli presented prior to or accompanying the eliciting stimulus (Hoffman & Searle, 1968;Ison & Hammond, 1971;Krauter, Leonard, & Ison, 1973).…”
mentioning
confidence: 99%
“…1988] noted similarities between microwave evoked body movements and classical startle reflexes. Startle is a protective response of mammals to an unexpected, sudden and intense visual, auditory, or tactile stimulus [Fleshier 1965]. Brown et al [1994] studied this effect in detail in mice exposed locally (head and neck) to 1.25 GHz microwave pulses ranging from 50 ms to 3.2 s. Results of this study arc shown in Table 1.…”
Section: Microwave Evoked Body Movementsmentioning
confidence: 83%
“…Intense stimulation, novel or not, tends to elicit a startle reaction. In its most developed form this consists in limb extension followed by generalized 244 Exploration flexion leading to a crouching posture, all within 10-20 ms of stimulation (Fleshler 1965, Horlington 1968. The crucial determinants of the startle reaction, which can be classified as a defensive reflex, are the intensity and suddenness of the stimulating event Hunt 1939, Fleshler 1965), where intensity is best conceived in terms of signal-to-noise ratios (Davis 1974).…”
Section: The Form Of Reactions To Novelty/noticeabilitymentioning
confidence: 99%